Avaliação do efeito local do paratormônio e da vitamina d no crescimento ósseo vertical guiado - Reisdoerfer, Gisele (2019)
Osteoconductive and osteoinductive agents have been extensively investigated to treat bone defects through guided bone regeneration. The aim of this study was to observe guided vertical bone growth in critical calvarial defects of rats treated with Vitamin D (VD) and Parathyroid hormone (PTH), evaluating the immunoexpression of sclerostin, BMP-2, OPG, IGF-1 and IP3R . Bone defects were created in the parietal bone of 42 male Wistar rats. Two defects were made in each animal, one of critical size, which served as an autogenous bone donor area, and another that was the study and analysis work area. In this there was descorticalization, filling with autogenous bone and fixation of resin helmet to promote guided regeneration. The autografted, PTH and Vitamin D groups were systemically treated intermittently with saline solution, 250 µg/ml, FortéoR Colter Pen - injectable, Lilly/kg e 4,3 ml/kg of Vitamin D respectively. After the healing periods of 15 and 60 days, bone blocks were removed, processed and histological, histomorphometric and immunohistochemical analyzes were performed. The statistical and descriptive analysis was done by the SPSS 18.0 program. We used one-way variance test, Shapiro-Wilk and KruskallWallis tests were applied (p<0.05). In animals receiving PTH, we observed improvement of vertical bone formation with increasing time, increased number of BMP- positive cells in the control and PTH groups, and decreased sclerostin immunoexpression. As well as increased immunoexpression of OPG, IGF-1 and IP3R in the cells analyzed by immunohistochemistry. We considered that in the presence of the PTH, the amount of bone formed under the resin helmet was satisfactory, associated with the improvement of the osteoconductive function of BMP-2 , inhibition of sclerostin, increased immunoblots for OPG, IGF-1 and IP3R.